ANALISIS COST – BENEFIT INJEKSI NaOH PADA BASIN COOLING TOWER PLTP UNIT 5 DAN 6 DI AREA GEOTHERMAL LAHENDONG - Romi Arifin; Agung Sutrisno; Charles Punuhsingon (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2019)
This study aimed to calculate and analyze the value of cost-benefit NaOH injection on cooling tower basin GPP unit 5 and 6 in the Lahendong geothermal area.Â Population of this study was worker (GPP), work partners and management (PGE). Analysis techniques used is cost benefit analysis. The result of the study showed that NaOH injection on cooling tower basin GPP unit 5 and 6 has impact routine expenses issued by company for the purchase NaOH because injection done every day to keep pH value on cooling tower basin GPP according to standard HSSE 5,5 - 7. The costs were not direct is building constructions to supplies NaOH reserve, coatings basin, and delivery expense. The result of the calculation cost-benefit analysis NaOH injection on cooling tower basin GPP unit 5 and 6 in the Lahendong geothermal area for 3 years investment and the operational as follows: (1)Benefit Cost Ratio (BCR) reach 1,2025697 > 0, (2)Net Benefit Margin (NBM) reach Rp. 337.955.950 > 0. Based on this value NaOH injection on cooling tower basin GPP unit 5 and 6 in the Lahendong geothermal area considered beneficial.Â Keyword: GPP, NaOH, Injection, Cooling Tower Basin, Cost-Benefit, BCR, NBM